Creativity and Creative Abilities Among General And Special Education Teachers - Elly Sukmanasa, Lina Novita, (International Journal of Management, Innovation, and Education, 2022)
Teachers' perceptions of creativity are an important key to understanding the creative process in the classroom. This study investigated differences in perceptions of creativity and potential for creativity between 59 special education teachers and 58 general education teachers. The Teacher Perceptions of Student Characteristics Survey was used to examine teachers' perceptions of their own creativity and of their desire for creativity-related traits among their students. The results showed that although teachers in both study groups considered themselves to have high levels of creativity and considered creativity to be the most important educational goal, most teachers preferred less creative characteristics among their students. This finding also highlights the differences between general education teachers and special education teachers in their perceptions of creativity and creative abilities. Finally, this study further assessed the contribution of teachers' background characteristics and their level of creativity to the overall ratings of desirable traits associated with creativity and traits that are contrary to creativity among their students.